Strategi Produksi Konten Visual @Creativismtudio di Instagram - Ismu Putra Herdrianto; Jokhanan Kristiyono (LPPM Stikosa-AWS, 2022)
This study aims to understand how the production process of visual content Production House @creativismstudio on Instagram. This research uses POAC management theory and new media. The method used is a case study with a descriptive qualitative approach. Data collection techniques were obtained by interviewing the owner of the Production House, conducting direct observations and collecting data in the form of supporting documents. The results of this study are 1) @creativistudio is very instrumental in maintaining and maximizing individual creative abilities to progress and develop and generate benefits for these individuals and clients who have entrusted the services of @creativsmstudio, 2) @creativismstudio really takes advantage of convergence in POAC management at the Production House these, 3) @creativsmstudio also utilizes new media in creating its audio visual production content by converging on the Instagram platform, 4) @creativsmstudio optimizes convergence efforts on other social media such as TikTok